2010
DOI: 10.1007/s11239-010-0506-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability in patients with type 2 diabetes mellitus detected by a thrombin generation assay

Abstract: Diabetes is a risk factor for the development of atherothrombosis and venous thromboembolism (VTE). We investigated whether plasma from patients with type 2 diabetes has an imbalance of pro- versus anti-coagulation resulting in hypercoagulability despite normal conventional coagulation tests. We analyzed blood samples from 60 patients with type 2 diabetes and 60 gender- and age-matched healthy subjects (controls) for the levels of pro- and anti-coagulant factors, for thrombin generation and for the numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 35 publications
4
99
1
4
Order By: Relevance
“…A hypercoagulable state, detected by thrombin generation tests, was reported in patients with T2D, explaining, at least partially, the high incidence of vascular events in these patients [9].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…A hypercoagulable state, detected by thrombin generation tests, was reported in patients with T2D, explaining, at least partially, the high incidence of vascular events in these patients [9].…”
mentioning
confidence: 92%
“…Improved glycemic control is the only significant predictor of a decrease in blood thrombogenicity, irrespective of treatment allocation [7]. Enhanced levels of prothrombin fragment 1+2 (F1+2) and thrombin-antithrombin complexes (TAT) have been shown in T2D patients in comparison with healthy subjects [8].A hypercoagulable state, detected by thrombin generation tests, was reported in patients with T2D, explaining, at least partially, the high incidence of vascular events in these patients [9].Platelets of patients with DM are characterized by dysregulation of several signaling pathways, leading to an hyperreactive phenotype with enhanced adhesion, aggregation, and activation [10]. Chronic hyperglycemia has been clearly identified as a causal factor for in vivo platelet activation [11].…”
mentioning
confidence: 99%
“…'nın venöz tromboemboli için yüksek riske sahip diabetes mellituslu hastalarda yaptığı çalış-mada, TGA testi ile venöz tromboembolinin ön-görülebileceği ve verilen mevcut tedavilerin veya trombini ve aktive F X'u inhibe etmeye yönelik Turkiye Klinikleri J Med Sci 2013;33 (3) yeni antikoagülan tedavilerin bu hastalarda faydalı olabileceği öne sürülmüştür. 36 Bizim çalışma-mızda da TA'da önemli bir yeri olan trombofilili hastalarda ve rutin testlerle trombofili göstergesi saptanamayan hastalarda ETP değerinin yüksek olmasının önemli olabileceğini, TA'sı olan hastalarda antikoagülan tedavi başlanmasında ve tedavinin takibinde bu testin yol gösterici olabileceğini düşünmekteyiz. Açıklanamayan TA'sı olan hastalarda antikoagülan kullanımına yönelik yapılan çalışmalarda TGA testi kullanıldığı takdirde hiperkoagülabilite tespit edilen hastaların ayrıca değerlendirilmesinin sonuçları etkileyebileceği kanaatindeyiz.…”
Section: Discussionunclassified
“…When thrombin is generated, the substrate is cleaved and makes a fluorescent signal, and several parameters are derived from the serial changes in the thrombin generation. It is considered that the TGA has the advantage of better detecting hypercoagulability than the aPTT or PT, and several clinical studies have shown its utility for detecting the hypercoagulability [6,7].…”
Section: Assessments Of Blood Coagulability Using Plasmamentioning
confidence: 99%